2021
DOI: 10.18553/jmcp.2021.27.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of ribociclib plus endocrine therapy versus placebo plus endocrine therapy in HR-positive, HER2-negative breast cancer

Abstract: BACKGROUND: The 2015 American Society of Clinical Oncology guidelines recommend first-line treatment of hormone receptor (HR)-positive breast cancer with endocrine therapy plus or minus palbociclib, a selective cyclin-dependent kinase (CDK)4/6 inhibitor. In 2018, the U.S. Food and Drug Administration approved ribociclib, a new orally available selective CDK4/6 inhibitor. While gains in progression-free survival (PFS) and overall survival (OS) from ribociclib are important for clinical and treatment outcomes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…After a comprehensive search based on the inclusion and exclusion criteria, a total of 15 articles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Results Of Literature Search and Quality Of The Included Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…After a comprehensive search based on the inclusion and exclusion criteria, a total of 15 articles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Results Of Literature Search and Quality Of The Included Literaturementioning
confidence: 99%
“…Eight studies were conducted in the United States (18,20,23,(25)(26)(27)(28)(29), 3 in China (24,26,28), and 1 each in Spain (15), the United Kingdom (16), Singapore (19), Canada (17), and Switzerland (21,22). One of the 14 studies did not describe the study perspective (25), 4 s t u d i e s a d o p t e d a h e a l t h s y s t e m p e r s p e c t i v e (15,19,21,22,24), 6 studies used a health insurance payer perspective (17,18,23,26,27,29), 1 study used a society-wide perspective (20), and 2 studies used both a health system perspective and a health insurance payer perspective (16,28). Study types included cost-effectiveness analysis (CEA) and/ or cost-utility analysis (CUA).…”
Section: Basic Features Of the Enrolled Studiesmentioning
confidence: 99%
“…Some recent studies have applied cost-effectiveness models to evaluate the CDK4/6 inhibitors, although differences in the measured outcomes and reported currencies limit comparisons between studies. [24][25][26][27] For example, Giuliani & Bonetti assessed the pharmacological costs of the three agents expressed in 2020 euros based on drug costs from a pharmacy in Italy and found that ribociclib was less expensive than abemaciclib and palbociclib. 25 The current study provides a novel comparison of the real-world economic burden for women with HR+/HER2-aBC receiving CDK4/6 inhibitors from a US payer's perspective, particularly as the three CDK4/6 inhibitors may differ in terms of efficacy and tolerability, which could have an impact on HRU and costs in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear clinical benefit of CDK4/6 inhibitors for the treatment of HR+/HER2-aBC, evidence is needed regarding their comparative healthcare resource utilization (HRU) and economic outcomes. Although several cost-effectiveness models in different countries have previously been published, [24][25][26][27] it is important to understand the real-world impact of these treatments from the payer perspective, particularly as all three CDK4/6 inhibitors may differ in terms of efficacy and tolerability which may impact HRU and healthcare costs. To help fill this knowledge gap, this study compares the HRU and healthcare costs of pre-and postmenopausal women diagnosed with HR+/HER2-aBC treated with ribociclib versus abemaciclib and ribociclib versus palbociclib in real-world practice from a US commercial payer perspective.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Two IPV-containing schedules were compared to the four-tOPV schedule, in terms of additional cost per VAPP case prevented and corresponding ICER. In addition, univariate sensitivity analysis was performed for key variables in the model, using Tornado plot as described elsewhere [30][31][32].…”
Section: Procurement Of Vaccinesmentioning
confidence: 99%